Effect of agricultural tractor axle load balancing on tillage efficiency and the soil physical and mechanical properties of a vertisol - Villagra-Mendoza, Karolina (2023)
Introduction. Due to the high worldwide rate of soil degradation, it is necessary to look for agricultural practices that promote soil conservation. Objective. To assess the tractor axle load balancing dedicated to tillage, through different counterweights distributions, to improve the physical, mechanical, and hydraulic properties of a vertisol and the efficiency of tillage operation. Materials and methods. Three different load balances were set on the front and rear axles, being 40-60%, 30-70% and 50-50%, by adding counterweights to the rear axle of the tractor. Field samples were taken at a depth of 15 cm in 3 sampling stages (before, immediately and 2 months after tillage), in a grass (Digitaria decumbens Stent) cultivated lot. Soil water content, bulk density, plastic limits, soil penetration resistance, as well as the water needs of the crop according to the treatments were analyzed. In addition, operation and efficiency variables were determined, such as tillage depth, slippage, fuel consumption, friction, and tractor power required. The differences of the variables between the treatments and sampling stages were analyzed to determine the treatment with the least impact to the soil properties and greater efficiency of operation. Results. Significant differences were found between balances in all the soil properties analyzed, except in the soil water content. The balance 30-70% presented the lowest values of fuel and water consumption for irrigation of the grass crop, wheel slippage, shear stress and penetration resistance. Conclusions. The balance treatment of 30-70% was considered as the best treatment under the studied conditions. Tillage with the treatment 50-50% was not recommended since tillage depth and soil property changes between sampling stages affected negatively to some soil properties.